IDENTIFIKASI DAN HISTOPATOLOGI Flavobacterium columnare PADA IKAN NILA (Oreochromis niloticus) - Andi Jumria; Novia Christi Prihartini; Alfiyah Alfiyah (Faculty of Science and Technology University Ibrahimy, 2017)
Flavobacterium columnare has been isolated from the cultivation of tilapia. Clinically, this bacterial infection is characterized by the occurrence of whitish gray changes in some parts of the head, around the mouth, gills, fins or body. The disease often ends in death, which causes great economic losses in the aquaculture industry. Of the 15 samples taken, only 5 samples showed clinical characteristics that were chronic. After tested by conventional method, only 3 samples showed F.columnare characteristic with bacterial colonies of pale yellow bacteria isolate with rhizoid edges, small size, long stem, gram negative and motile. The results of histopathologic testing of muscle organs, fins and gills, showed the presence of bacterial colonies suspected of F. colloid in muscle and also some necrosis points. In the kidney there are many macrophages and infiltration of inflammatory cells, while on the fins seen the existence of congestion and inflammatory cells. The gill damage found was hyperplasia that developed into fusion, congestion and necrosis.